Fermenter : DIY fermentation for vegan fare - Adams, Aaron (Chef); Crain, Liz (Sasquatch Books, 2023)
"Fermenter specializes in fermentation from a fully plant-based perspective--hand-crafting their own tempeh, vegan cheeses, kombucha, and koji and putting it all together to make comforting, craveable dishes"--